ACCOUNTABILITY PRACTICES OF SPECIAL HAJJ AGENCIES: A STUDY USING STEWART’S LADDER - Annisa, Ellis; Suandi, Aprilia Beta (Multazam : Jurnal Manajemen Haji dan Umrah, 2025)
This study examines the accountability practices of Special Hajj Organizers (PIHK) in Yogyakarta Province using Stewart’s (1984) accountability ladder, which includes five levels: honesty and legality, process, performance, program, and policy accountability. A qualitative approach was used, with data collected through interviews and documents related to PIHK accountability. The study involved five key informants consisting of PIHK leaders, finance staff, and pilgrims from PT Citra Wisata Dunia and PT Al Anshor Madinah Barokah. The findings show strong accountability practices at the levels of honesty and legality, process, performance, and program accountability. However, policy accountability appears weak due to the lack of triangulable sources and data. This study is the first to investigate accountability in the special Hajj services managed by travel agencies. Previous studies have focused on accountability in religious organizations, overlooking accountability in religious rituals that require economic information, such as the Hajj pilgrimage.